Signaling from the Secretory Granule to the Nucleus: Uhmk1 and PAM - Francone, Victor P. (The Endocrine Society, 2010)
Neurons and endocrine cells package peptides in secretory granules (large dense-core vesicles) for storage and stimulated release. Studies of peptidylglycine α-amidating monooxygenase (PAM), an essential secretory granule membrane enzyme, revealed a pathway that can relay information from secretory granules to the nucleus, resulting in alterations in gene expression. The cytosolic domain (CD) of PAM, a type 1 membrane enzyme essential for the production of amidated peptides, is basally phosphorylated by U2AF homology motif kinase 1 (Uhmk1) and other Ser/Thr kinases. Proopiomelanocortin processing in AtT-20 corticotrope tumor cells was increased when Uhmk1 expression was reduced. Uhmk1 was concentrated in the nucleus, but cycled rapidly between nucleus and cytosol. Endoproteolytic cleavage of PAM releases a soluble CD fragment that localizes to the nucleus. Localization of PAM-CD to the nucleus was decreased when PAM-CD with phosphomimetic mutations was examined and when active Uhmk1 was simultaneously overexpressed. Membrane-tethering Uhmk1 did not eliminate its ability to exclude PAM-CD from the nucleus, suggesting that cytosolic Uhmk1 could cause this response. Microarray analysis demonstrated the ability of PAM to increase expression of a small subset of genes, including aquaporin 1 (Aqp1) in AtT-20 cells. Aqp1 mRNA levels were higher in wild-type mice than in mice heterozygous for PAM, indicating that a similar relationship occurs in vivo. Expression of PAM-CD also increased Aqp1 levels whereas expression of Uhmk1 diminished Aqp1 expression. The outlines of a pathway that ties secretory granule metabolism to the transcriptome are thus apparent.